2020
DOI: 10.1101/2020.09.14.296616
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ligation bias is a major contributor to nonstoichiometric abundances of secondary siRNAs and impacts analyses of microRNAs

Abstract: Plant small RNAs are a diverse and complex set of molecules, ranging in length from 21 to 24 nt, involved in a wide range of essential biological processes. High-throughput sequencing is used for the discovery and quantification of small RNAs. However, several biases can occur during the preparation of small RNA libraries, especially using low input RNA. We used two stages of maize anthers to evaluate the performance of seven commercially-available methods for small RNA library construction, using different RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…Specifically, the miR845 family increased until occupying close to 45% of the all sRNAs at pollen maturity ( Figure 1D ). Although this relative enrichment could be due to a bias in sRNA sequencing ( Baldrich et al, 2020 ), we found a consistent and significant detection of this increase in trinuclear and mature pollen sRNA libraries ( Figure 1, D, E , and I ). We confirmed this accumulation trend by sRNA gel blot for miR845, miR156, and miR161.1, which increased, maintained, and decreased their accumulation level respectively ( Figure 1F; Supplemental Figure S1, D and E ).…”
Section: Resultssupporting
confidence: 59%
“…Specifically, the miR845 family increased until occupying close to 45% of the all sRNAs at pollen maturity ( Figure 1D ). Although this relative enrichment could be due to a bias in sRNA sequencing ( Baldrich et al, 2020 ), we found a consistent and significant detection of this increase in trinuclear and mature pollen sRNA libraries ( Figure 1, D, E , and I ). We confirmed this accumulation trend by sRNA gel blot for miR845, miR156, and miR161.1, which increased, maintained, and decreased their accumulation level respectively ( Figure 1F; Supplemental Figure S1, D and E ).…”
Section: Resultssupporting
confidence: 59%
“…In our hands, NEB was the protocol that showed the highest reproducibility between replicas and that resulted in the highest number and variety of miRNAs, followed by NEXT and SMARTer. Our results are consistent with other studies [41][42][43] and reinforce the choice of NEB over other protocols because it is an easy-handling procedure specially applicable to low-input material, as is the case of clinical samples. As a second option, and depending on the source of the input material, the NEXT protocol might be the library preparation of choice [25,44].…”
Section: Discussionsupporting
confidence: 92%
“…However, it must be assumed that this is not the case when comparing between liquid biopsy sample types with very specific RNA compositions [19] or between different individuals [34]. Lutzmayer et al recognized this need in the context of plant microRNA research [33,35], but the adaptation of the technology to mammalian species as well as liquid biopsies was still missing.…”
Section: The Value Of Spike-ins For Small Rna Sequencingmentioning
confidence: 99%